Left ventricular non-compaction cardiomyopathy associated with the PRKAG2 mutation - Jing Zhang; Xiu Han; Qun Lu; Yunfei Feng; Aiqun Ma; Tingzhong Wang (BMC, 2022)
Abstract Left ventricular non-compaction cardiomyopathy (LVNC) is one of the most common inherited cardiovascular diseases. The genetic backgrounds of most LVNC patients are not fully understood. We collected clinical data, family histories, and blood samples and performed genetic analysis using next-generation sequencing (NGS) from a Chinese family of 15 subjects. Clinically LVNC affected subjects showed marked cardiac phenotype heterogeneity. We found that these subjects with LVNC carried a missense heterozygous genetic mutation c.905G>A (p.R302Q) in γ2 subunit of AMP-activated protein kinase (PRKAG2) gene through NGS. Individuals without this mutation showed no symptoms or cardiac structural abnormalities related to LVNC. One subject was the victim of sudden cardiac death. To sum up, PRKAG2 mutation c.905G>A (p.R302Q) caused familial LVNC. Our results described a potentially pathogenic mutation associated with LVNC, which may further extend the spectrum of LVNC phenotypes related to PRKAG2 gene mutations.